Alpha Asymmetry in Infants at Risk for Autism Spectrum Disorders - Gabard-Durnam, Laurel (2015)
An emerging focus of research on autism spectrum disorder (ASD) targets the identification of early-developing ASD endophenotypes using infant siblings of affected children. One potential neural endophenotype is resting frontal electroencephalogram (EEG) alpha asymmetry, a metric of hemispheric organization. Here, we examined the development of frontal EEG alpha asymmetry in ASD high-risk and low-risk infant populations. Our findings demonstrate that low and high-risk infants show different patterns of alpha asymmetry at 6 months of age and opposite growth trajectories in asymmetry over the following 12 months. These results support the candidacy of alpha asymmetry as an early neural ASD endophenotype.